Reduced occurrence of tumor flare with flavopiridol followed by combined flavopiridol and lenalidomide in patients with relapsed chronic lymphocytic leukemia (CLL). Issue 4 (25th February 2015) - Maddocks, Kami; Wei, Lai; Rozewski, Darlene; Jiang, Yao; Zhao, Yuan; Adusumilli, Mikhil; Pierceall, William E.; Doykin, Camille; Cardone, Michael H.; Jones, Jeffrey A.; Flynn, Joseph; Andritsos, Leslie A.; et al.
Abstract : Flavopiridol and lenalidomide have activity in refractory CLL without immunosuppression or opportunistic infections seen with other therapies. We hypothesized that flavopiridol treatment could adequately de‐bulk disease prior to lenalidomide therapy, decreasing the incidence of tumor flare with higher doses of lenalidomide. In this Phase I study, the maximum tolerated dose was not reached with treatment consisting of flavopiridol 30 mg m −2 intravenous bolus (IVB) + 30 mg m −2 continuous intravenous infusion (CIVI) cycle (C) 1 day (D) 1 and 30 mg m −2 IVB + 50 mg m −2 CIVI C1 D8, 15 and C2‐8 D3, 10, 17 with lenalidomide 15 mg orally daily C2‐8 D1‐21. There was no unexpected toxicity seen, including no increased tumor lysis, tumor flare (even at higher doses of lenalidomide) or opportunistic infection. Significant clinical activity was demonstrated, with a 51% response rate in this group of heavily pretreated patients. Biomarker testing confirmed association of mitochondrial priming of the BH3 only peptide Puma with response.Am. J. Hematol. 90:327–333, 2015. © 2015 Wiley Periodicals, Inc.